The Evolution of China's High-Level Talent Mobility Network: A Comparative Analysis Based on School and Work Stage. (24th January 2022) - Zhang, Fangfang; Liu, Hui; Zhang, Juntao; Cheng, Yi
Abstract : The flow of high-level talents in China is becoming more and more active and has a profound impact on the innovation and development of cities. Based on the research on the spatial distribution of the school and work stages of high-level talent in China, we study the structure and evolution of China's high-level talent mobility network by using the data on the flow trajectory of talent among cities in China. The results show that: (1) the spatial distribution of talents in the two stages has greater consistency, but there is a change characteristic of "large dispersion, small agglomeration." (2) Compared with the school stage, the network in the work stage has much more connections; the centrality gap of cities has narrowed. (3) "Core-periphery" structure of two networks is relatively significant and similar. The core layer in the two networks has not changed, but the subcore layer and the subedge layer have undergone changes. In addition, talents mainly flow to core and subcore cities. (4) The space structure of network is more complex in the work stage, and it is expanding to the Guangdong-Hong Kong-Macao Greater Bay Area in southeastern China.